2018
DOI: 10.1089/pho.2018.4476
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effect of Pulsed Nd:YAG Laser in the Treatment of Patients with Rotator Cuff Tendinopathy: A Randomized Controlled Trial

Abstract: Pulsed Nd:YAG laser combined with an exercise program seems to be more effective in the treatment of patients with rotator cuff tendinopathy than a sham laser with exercises.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 41 publications
2
30
0
1
Order By: Relevance
“…For example, one study showed that pulsed yttrium aluminium garnet (YAG) laser combined with exercise was more effective for treatment of rotator cuff tendinopathy than sham laser treatment with exercise. 34 Future randomized controlled trials should examine the combined effects of CARE and exercise, as most studies have shown no difference in outcome between impingement syndrome patients randomized to surgical decompression or conservative management. 35 Thus, it is always desirable to start with conservative rehabilitation treatment, administering surgical treatment only in select cases.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study showed that pulsed yttrium aluminium garnet (YAG) laser combined with exercise was more effective for treatment of rotator cuff tendinopathy than sham laser treatment with exercise. 34 Future randomized controlled trials should examine the combined effects of CARE and exercise, as most studies have shown no difference in outcome between impingement syndrome patients randomized to surgical decompression or conservative management. 35 Thus, it is always desirable to start with conservative rehabilitation treatment, administering surgical treatment only in select cases.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of laser therapy should be judged with caution; however, as only one trial ( n = 60 participants) provided direct evidence regarding its effect. 35 Pooled results suggested that exercise remained favourable over both corticosteroid injection (SMD 0.28, 95% CI 0.07, 0.49) and control arms (SMD 0.39, 95% CI 0.18, 0.59), as seen in pairwise meta-analysis, as well as compared with regenerative injections (0.53, 95% CI 0.15, 0.91).…”
Section: Resultsmentioning
confidence: 91%
“…For example, our results indicate that both laser therapy and exercise may provide benefits for patients for both pain and function outcomes across different follow-up time-points, with larger effects for exercise in the longer term. It must be noted, however, that only one relatively small trial 35 ( n = 60) with large uncertainty around its estimate of effects and with considerable risk of bias provided direct evidence regarding the effect of laser therapy. A larger number of trials provided evidence for the benefits of exercise, and these results (up until 3-month follow-up) were considered robust in sensitivity analyses excluding trials at increased risk of bias related to randomisation and data presentation or analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Ambos efectos se producen por la generación de calor en el tejido enfermo -un aumento de aprox. 2 ° C -3 ° C-y la estimulación mecánica de nociceptores y otras terminales nerviosas (21)(22) . En consecuencia, la HIL se ha convertido en una opción de tratamiento fiable, segura y eficaz en el tratamiento de diversas afecciones musculoesqueléticas (23) .…”
Section: Discussionunclassified